A canine thromboembolic model of anterior circulation large vessel occlusion stroke. Issue 4 (April 2023) - Zakeri, Amanda S.; Wheeler, Debra G.; Huttinger, Allyson; Carfora, Arianna; Kini, Aarushi; Stork, Taggart; Yacoub, Simon; Anderson, Cole; Joseph, Matthew; Shujaat, Mohammed T.; Nimjee, Shahid M.
Abstract: Purpose: To develop a large animal preclinical model of thromboembolic stroke with stable, protracted large vessel occlusion (LVO) utilizing an autologous clot. Materials and methods: A reproducible canine model of large vessel occlusion stroke was established by endovascular placement of an autologous clot into the middle cerebral artery (MCA) of six adult hounds and confirmed using digital subtraction angiography (DSA). Infarct volume and evidence of hemorrhage were determined by magnetic resonance imaging (MRI) 7 h after occlusion and Thrombolysis in Cerebral Infarction scale (TICI) was assessed before and after clot placement and at 1, 6, 7, and 9 h after middle cerebral artery occlusion (MCAO). Heart rate (HR) and blood pressure (BP) were monitored continuously and invasively through an arterial sheath throughout the procedures and complete blood count and blood gas analysis completed at time of sacrifice. Histopathological findings at time of sacrifice were used to confirm stroke volume and hemorrhage. Results: MCAO with resulting TICI 0 flow was observed in all six animals, verified by serial DSA, and lack of collateral flow persisted for 9 h after clot placement until time of sacrifice. The mean infarct volume was 47.0 ± 6.7% of the ipsilateral hemisphere and no events of spontaneous recanalization or clot autolysis were observed. Conclusion: We demonstrate a thromboembolic canine model of MCAO that is both feasible and results in consistent infarct volumes to generate a clinically relevant LVO. This model is important to evaluate treatment of LVO in acute ischemic stroke (AIS) outside the established 4.5 h recombinant tissue plasminogen activator (rTPA) therapeutic window utilizing a prolonged occlusive thrombus.